PENGELOLAAN SAMPAH RUMAH TANGGA DI KELURAHAN AEK PAROMBUNAN KOTA SIBOLGA - Elisa, Elisa; Ginting, Nurmaini; Rezeki, Happy Sri; Batubara, Melvariani Syari (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The problem in this research is to foster a community culture of the importance of a clean and healthy environment through waste management in their respective households. In this way, every member of the community is encouraged to care about the environment so that the environment remains clean and healthy because the waste problem absolutely must be handled optimally. The aim of this research is how to manage waste and the correlation between education level, family income level, behavior towards environmental cleanliness, knowledge about waste regulations. This research uses an observational analytical design. The relationship between the independent variable and the dependent variable is studied by taking momentary measurements and then conducting a correlation test. Household waste management in the Aek Parombunan sub-district has not been implemented optimally. Level of education, family income level, behavior towards environmental cleanliness, knowledge of waste regulations and willingness to pay levies waste is positively correlated with the way household waste is managed. The type of planning that can be applied in managing household waste in Aek Parombunan sub-district is transactive or social learning. Starting with fulfilling operational technical needs, namely household containerization and composting, communal waste sorting, village waste collection points for recycling, and sub-district TPS. Then increase community participation through empowerment and assistance by waste managers and other related agencies.